2012
DOI: 10.3748/wjg.v18.i22.2813
|View full text |Cite
|
Sign up to set email alerts
|

Patatin-like phospholipase domain containing-3gene I148M polymorphism, steatosis, and liver damage in hereditary hemochromatosis

Abstract: The PNPLA3 I148M polymorphism may represent a permissive factor for fibrosis progression in patients with C282Y+/+ HH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…The association between the I148M variant and NAFLD holds true both in adults and in adolescents [64][65][66][67][68]; I148M allele homozygosity predisposes to NASH and hepatic fibrosis [56][57][58]. The association between the I148M variant and fibrosis is also evident in chronic viral hepatitis and genetic diseases, such as hereditary haemochromatosis [69][70][71]. In addition, the I148M variant predisposes to hepatocellular carcinoma (HCC), independently of the aetiology of chronic liver disease, and homozygous patients have a worse prognosis [72][73][74][75][76].…”
Section: Geneticsmentioning
confidence: 95%
“…The association between the I148M variant and NAFLD holds true both in adults and in adolescents [64][65][66][67][68]; I148M allele homozygosity predisposes to NASH and hepatic fibrosis [56][57][58]. The association between the I148M variant and fibrosis is also evident in chronic viral hepatitis and genetic diseases, such as hereditary haemochromatosis [69][70][71]. In addition, the I148M variant predisposes to hepatocellular carcinoma (HCC), independently of the aetiology of chronic liver disease, and homozygous patients have a worse prognosis [72][73][74][75][76].…”
Section: Geneticsmentioning
confidence: 95%
“…Interestingly, our fi ndings differ from that reported in a study that was not eligible for inclusion in our meta-analysis. Specifically, in a study of Italian patients with hereditary hemochromatosis, Valenti et al ( 33 ) did not fi nd any association between cirrhosis and the G allele or the GC or GG genotype. Subanalysis, however, did reveal a signifi cant association between cirrhosis and the G allele in patients with a [ Q = 10.97, degrees of freedom (df) = 6, P = 0.089, I 2 = 45.31%].…”
Section: Discussionmentioning
confidence: 99%
“…One study from Italy reported a significant association between PNPLA3 and steatosis/advanced fibrosis in 174 patients with hereditary hemochromatosis and homozygous for the HFE C282Y mutation [47]. However, the association with cirrhosis was not replicated in another study that also included patients of European descent [48].…”
Section: Other Liver Diseasesmentioning
confidence: 99%